Apakah Sistem Informasi Akuntansi Dapat Memoderasi Faktor Yang Mempengaruhi Pengendalian Internal - Robiur Rahmat Putra; Yhoga Pranata (Owner : Riset dan Jurnal Akuntansi, 2022)
Weak internal controls often lead to the creation of anti-fraud and corruption policies and the role accounting can play in increasing accountability and transparency through auditing and regulation. This study aims to provide recommendations and strategies to companies related to the implementation of internal control. The population in this study are employees who work in the finance & accounting department in Jabodetabek. The number of samples in this study were 216 respondents with data collection techniques using questionnaires. The data analysis technique used in this study uses Structural Equation Modeling (SEM) with the help of PLS. The results of this study indicate that accounting knowledge has no effect on internal control, ethics has an influence on internal control, accounting information systems have an influence on internal control, accounting information systems are not able to moderate knowledge on internal control, and accounting information systems are not able to moderate professional ethics. to internal control. The implication of the results of this study is to recommend to companies related to efforts to implement internal control so that they can pay more attention to professional ethics and accounting information systems, because this study proves that professional ethics and accounting information systems affect internal control. In addition, the company must apply a strategic way that is in accordance with the needs of the company implementing internal controls such as providing education, training, and motivation for employees in supporting the work of course this is also one of the strategic ways in implementing internal control.